An investigation into the ancestry of the Malagasy population using variation in the alpha- and beta-globin gene cluster - Hewitt, Rachel (My University, 2014)
The issue of Malagasy ancestry has been controversial, and has still not been completely resolved. The historical, linguistic, archaeological and some genetic evidence points to the fact that modern Malagasy are the descendants of immigrants who arrived on the island over the past 2000 years, from South and Southeast Asia, Africa and the Near East. In more recent centuries, mainly in the twentieth century, there have been significant numbers of Indian, Chinese and French immigrants. In addition, archaeological and historical studies of specific regional populations of Malagasy suggest a complex pattern of internal migration within the island, extending back in time to the first European contacts with the island in the sixteenth century. The 22 Malagasy ethnic groups may be classified as "highland" or "lowland" depending on their geographic distribution on the island. Within the ethnic groups, the founding populations have made different genetic contributions: the highland groups are said to have a greater Indonesian contribution to their ancestry, while the lowlanders have a greater African contribution to their ancestry. Genetic studies on the Malagasy have been limited by small sample sizes, deficiencies in sampling procedures and in the limited number of polymorphisms studied. In light of the paucity of written records, the Department of Human Genetics, SAIMR, has undertaken a large study in Madagascar to reconstruct the biological history of its people, using genetic variation. This thesis forms a part of this study. Variation in the a- and p-globin cluster has been extensively studied in many parts of the world, and has been shown to be population specific, with specific variants having distinct geographical distributions. Thus haemoglobin and its related disorders have been the subject of extensive studies for determining the origin(s) of particular populations. In this study, some of the a- and p-globin variation present in the Malagasy was characterised. Seven RFLPs/HVRs in the a-globin gene cluster and seven RFLPs in the p-globin gene cluster were analysed. The common a- and p-globin gene cluster haplotypes differ between African and Asian populations. Frequencies also vary between populations in a specific geographical regions. The aim of this study was to characterise the haplotypes present in the Malagasy, to provide information on the relative genetic contributions of different populations to the peoples of Madagascar. DNA samples from randomly selected, haematologically normal individuals were analysed. Individuals were chosen from six Malagasy ethnic groups: two “highland” populations (Merina and Betsileo), two “lowland" populations (Antasaka and Tsimiheti) and two populations from the south-west of the island (Mahafaly and Vezo). The groups chosen cover a broad range of Madagascar and thus provide some representation of the Malagasy population as a whole. The number of individuals studied in each ethnic group are as follows: Merina: 88; Betsileo: 78; Antasaka: 67; Tsimiheti: 67; Mahafaly: 26; Vezo: 25. The frequencies of the a- and (B-globin RFLP sites and a-globin HVRs in the Malagasy vere calculated. 5' and 3’ p-globin haplotypes were constructed on the basis of homozygosity. A maximum-likelihood algorithm was used to obtain frequencies of 5’ P-globin haplotypes that could not be assigned on the basis of homozygosity. These data were then subject to statistical analysis. The frequencies of the 5’ p-globin haplotypes (consisting of the five sites Hindi 5' to e, Hindi 11 within Gy and Ay, Hindi within \|/P and 3' to it) were the most informative data set for comparing the Malagasy ethnic groups to each other and to other world populations. Unfortunately, the maximum-likelihood estimates of 5‘ p-globin haplotypes could not be used for comparative analyses due to the lack of similar data in other populations. However the strong correlation between the maximum-likelihood frequencies and the observed frequencies illustrated the ability of the algorithm to determine hapiotype frequencies from otherwise uninformative individuals. 5’ p-globin haplotypes were assigned unambiguously for 248 Malagasy chromosomes. Ten haplotypes were found; of these, nine have been reported previously in other world populations and one has not been reported and hns thus been called “rare” in this study. The frequencies of unambiguous 5’ p-globin haplotypes in the Malagasy and the proposed parental populations were initially analysed with x2 tests. For a more accurate comparison between these populations, genetic distances were calculated and used for the construction of phylogenetic trees, principle component analysis was carried out, and a study of heterozygosity versus distance from the centroid was performed. Admixture estimates of two African populations and one Indonesian population to Malagasy ancestry were calculated. Certain general trends were noted in all the analyses. The results are in agreement with the historical data which provides evidence for both African and Asian contributions to Malagasy ancestry. The highlanders were more closely affiliated to the Indonesian/Polynesian populations, while the south-west groups showed the strongest associations with the African populations. The lowlanders were consistently intermediate in position between the highlanders and the south-west groups, with the Antasaka being slightly more closely related to the African populations than the Tsimiheti. The Malagasy were shown to have high heterozygosities, similar to those of African populations, and this high degree of diversity is probably a reflection of the many sources of ancestry of the Malagasy. The south-west groups were the furthest outliers in the model of heterozygosity versus distance from the centroid, suggesting that these groups are the most genetically admixed of all the Malagasy groups that were studied. Estimates of ancestral population admixture confirmed these trends, with the highlanders having the highest proportional contribution by Indonesians (53%), but the lowest total African contribution (47%), while the south-west groups have the highest Bantu contribution (65%). The Indonesian and African contributions to the lowlanders are intermediate between those to highlanders and south-west groups. Overall the Malagasy subjects included in this study showed a 61% African admixture contribution and a 39% Indonesian admixture contribution. It is hoped that the results obtained in this study will contribute to the larger project concerning the origins of the Malagasy, and that they may be used to shed further light on the much debated issue of Malagasy ancestry.
Thesis (M.Sc. (Med.))--University of the Witwatersrand, Faculty of Health Sciences, 1998.
Keywords: Genetics, Population; Hemoglobins, Abnormal; Variation (Genetics)